Demonstratives in Spatial Language and Social Interaction: An Interdisciplinary Review - Diessel, Holger; Coventry, Kenny R. (Frontiers in Psychology, 2020)
This paper offers a review of research on demonstratives from an interdisciplinary perspective. In particular, we consider the role of demonstratives in current research on language universals, language evolution, language acquisition, multimodal communication, language and perception, language in interaction, spatial imagery, and discourse processing. Traditionally, demonstratives are analyzed as a specific class of spatial deictics. Yet, a number of recent studies have argued that space is largely irrelevant to deixis and that demonstratives are primarily used for social and interactive purposes. Synthesizing findings in the literature, we conclude that demonstratives are a particular class of linguistic items that are foundational to both spatial and social aspects of language and cognition.